2017
DOI: 10.1017/s1751731117000143
|View full text |Cite
|
Sign up to set email alerts
|

Exposing broiler eggs to green, red and white light during incubation

Abstract: Previous work has shown that exposing broiler eggs to white light during incubation can improve hatchability and post-hatch animal welfare. It was hypothesized that due to how different wavelengths of light can affect avian physiology differently, and how pigmented eggshells filter light that different monochromatic wavelengths would have differential effects on hatchability and post-hatch animal welfare indicators. To determine, we incubated chicken eggs (n = 6912) under either no light (dark), green light, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 35 publications
4
35
1
1
Order By: Relevance
“…Significant differences for early, mid and late embryonic mortality percentages among different light colors were recorded by (Shafey and Al-Mohsen, 2002). But non-significant differences among different light colors were recorded by (Archer 2017).…”
Section: Embryonic Mortalitiesmentioning
confidence: 85%
See 3 more Smart Citations
“…Significant differences for early, mid and late embryonic mortality percentages among different light colors were recorded by (Shafey and Al-Mohsen, 2002). But non-significant differences among different light colors were recorded by (Archer 2017).…”
Section: Embryonic Mortalitiesmentioning
confidence: 85%
“…In addition, Hluchý et al (2012) had similar findings to this present study as Red light increasing hatchability. Archer (2017) found that the Red and White light treatments had a higher hatch of fertile eggs than those of both Green and Dark treatments, but he found that Green light did not improve hatchability in his study suggesting that the wavelength of light responsible for increased hatchability. On the other hand, this result disagreed with Bowling et al (1981) who reported a reduction in hatchability of White Leghorn eggs due to white lighted incubation.…”
Section: Fertility and Hatchabilitymentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, providing light during incubation has no negative effect on production or health of broilers (Archer, et al, 2009). Recently, it has been shown that exposing broiler eggs to white light and red light that is a component of it are possibly the key spectrum to improving hatchability and lower fear and stress susceptibility, whereas green light is not as effective during incubation (Archer, 2017). These studies have been conducted with eggs from fast-growing broilers, and it would be interesting to investigate how light provision during incubation of eggs from slow-growing broilers may affect behaviour and welfare of these birds in the post-hatch rearing period.…”
Section: Effects Of Light During Incubationmentioning
confidence: 99%